Evaluation of Reconstruction Parameters for Two-Dimensional Comb-push Ultrasound Shear Wave Elastography - Racedo, Jorge (IEEE Trans Ultrason Ferroelectr Freq Control, 2018)
Shear wave elastography (SWE) is a noninvasive ultrasound imaging modality used in the assessment of the mechanical properties of tissues such as the liver, kidney, skeletal muscle, thyroid and the breast. Among the methods used to perform SWE is the comb- push ultrasound shear elastography (CUSE) method. This method uses multiple focused ultrasound beams to generate push beams with acoustic radiation force. Applying these push beams generates propagating shear waves. The propagation motion is measured with ultrafast ultrasound imaging. The shear wave motion data is directionally filtered, and a two-dimensional shear wave velocity algorithm is applied to create group velocity maps. This algorithm uses a moving window and a specified patch for performing cross-correlations of time-domain signals. We performed a parametric study of how the choice of the patch and window size affected the reconstruction of the shear wave velocity in homogeneous and inclusion phantoms. We quantified the mean velocity and coefficient of variation in the homogeneous phantoms. We measured the contrast-to-noise ratio and bias in the inclusion phantoms. In each of these cases, we found that particular combinations of the patch and window provided optimal values of these evaluation metrics for the phantoms tested. This study provides a basis to construct algorithms to produce optimal shear wave velocity reconstructions for various clinical applications.